Understanding of Polygamy in the Qur’anic Text, Hadith Text, and Biblical Text - Rohmansyah Rohmansyah (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2019)
The difference in views that often arises and becomes the latest issue in the context of family law is polygamy. Polygamy is misunderstood as something that is frightening for some people so it needs to be shunned. This paper aims to explain various views about polygamy according to the Qur'anic text, hadith text and bible text. The method used is library research with a sociological-historical approach. The results of this study found several things, namely: polygamy in the text of the Koran and the hadith of the Prophet there are similarities and no differences were found, even the hadith of the Prophet became a reinforcement of the Koran about the limits of permissibility of polygamy with conditions apply fairly. Whereas polygamy in the text of the Bible is permitted without limitation on the number of women being polygamy and not being fair, even though Christians forbid polygamy.